#TITLE_ALTERNATIVE# - MOSADY PUTRA (NIM : 12304031), ALKHWARIZMI
Eastern Indonesia famed with complexity of structural pattern and complicated of geology evolution. One of most complex tectonic systems region in the eastern Indonesia is Banda arc, which have several different fitures with other islands arc. One of it is lateral bending counter-clockwise in easternmost Banda arc which can marked by morfology of islands arc and hipocenter depth contour. Besides, seismicity in Banda arc showing difference in case of dip-direction trend. In the Timor trough, Aru trough, and Seram rough, seismicity dip-direction trend to north, west to northwest, and southwest, respectively, so overall subducted slab lithosphere beneath Banda arc form a basin-like structure. Therefore, comprehensive study with using geophisical data is necessary for delineated geometry lithospheric slab beneath Banda arc. Focus on this study is to know geometry lithospheric slab beneath Banda arc using seismicity study, focal mechanism solutions, and seismic tomogram, with coverage area study is 115°-140°E and 0°-15°S. The process is by determining depth coordinate of top seismicity in each cross-section seismicity and then interpolated it, so we obtained three dimansional surface slab. From focal mechanism data, we analyse how orientation principal stress axis in Banda arc, and from seismic tomogram data we will reconstruct three dimensional surface of slab lithosphere beneath Banda arc beneath 410 Km depth (beneath mantle transition zone) to know deflection character of the lithospheric slab. The result of interpolation top seismicity depth showing shape of lithospheric slab beneath Banda arc forming spoon shaped structure opened to west. Three dimensional reconstruction high-speed wave anomaly clearly showing excees lithospheric slab material in the uppermost lower mantel in the bend part of slab, and deflection lithospheric slab subducted in Timor trough form 'kink' structure which elongated laterally with elongation direction same as subduction direction. Focal mechanism solution showing shallow earthquake in Aru Trough dominated by normal earthquake in trench axis and reverse earthquake in Seram Trough. Shallow earthquake in back-arc, particularly around Banda Sea, dominated by strike slip and reverse earthquake, with P-axis direction consistent to north-south. Intermediate earthquake characterized by down dip tension type, and deep earthquake generally is down dip compression.